2021
DOI: 10.24042/tadris.v6i1.6295
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Prosocial Behavior on Student of Islamic and Public Schools at Banda Aceh, Indonesia

Abstract: This study aimed to examine religiosity's relationship with prosocial students' behavior in Aceh, Indonesia. This research was a quantitative survey using cross-sectional studies and data collected from selected individuals over a specific period. The researchers collected data from 649 students (299 male and 350 females) using a non-proportional stratified sampling. Data were collected using two questionnaires, (1) Islamic Religiosity by using SPPIM-R and (2) Prosocial Behavior by using PTM-R. The data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…Nur (2018) also found that religious values have already included all other values such as independence, nationalism, mutual cooperation, and integrity. Another research supported the notion that religiosity is negatively related to academic dishonesty (Khan et al, 2019) while positively related to moral behavior (Azizah, 2015), moral competence (Zubairu, Dauda, Paiko, & Sakariyau, 2017), and prosocial behavior (Safrilsyah, Zailani, Khairi, & Ibrahim, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Nur (2018) also found that religious values have already included all other values such as independence, nationalism, mutual cooperation, and integrity. Another research supported the notion that religiosity is negatively related to academic dishonesty (Khan et al, 2019) while positively related to moral behavior (Azizah, 2015), moral competence (Zubairu, Dauda, Paiko, & Sakariyau, 2017), and prosocial behavior (Safrilsyah, Zailani, Khairi, & Ibrahim, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Dan Setelah berjalannya proses perkuliahan secara daring banyak mahasiswa justru mengalami kesulitas belajar (Rusmaladewi et al, 2020). Hal lain membuat informan ter-motivasi belajar karena adanya pengaruh dari bentuk religiusitas hal ini sesuai dengan penelitian yang dilakukan (Safrilsyah et al, 2021) dan semangat religius mampu memberikan makna, pencerahan, dan perubahan masa depan peserta didik secara tepat terutama da-lam belajar. Dan dilanjutkan dalam penelitian (Salsabila et al, 2021).…”
Section: Metode Penelitianunclassified
“…Islamic religious education has broader goals than general education, namely building good personal character and developing broad religious knowledge (Safrilsyah et al, 2021). The internalization of religious values is an important basis for Muslim students in developing their interpersonal intelligence.…”
Section: A Introductionmentioning
confidence: 99%